The critical evaluation of how age influences founders' leadership style within small firms in Nigeria - Enearu, Michael (2017)
Leadership is important to how organisations function, similarly, leadership styles are fundamental to the foundation and growth of many firms; as well as critical in terms of how firms sustain and position themselves heading into the future. Similarly, the role of entrepreneurial leadership is important to organisational success and its functions. However, while entrepreneurship and leadership research has focused more on developed countries; developing countries have not received as much attention, regardless of the fact that more entrepreneurial activities take place within developing economies. The same can be said for research on age and leadership, as few empirical research have been carried out in that field, regardless of its importance. This dissertation seeks to add to the body of literature in entrepreneurship and leadership field by evaluating how age influences founders’ leadership styles within small firms in Nigeria, with particular focus on younger leaders- the emphasis on younger leaders is because it is known that entrepreneurs tend to create new ventures around the age of thirty or younger. The dissertation also evaluates the perceptions held about the leaders and their leadership style by the employees of these firms. Using case study and interview methods in tandem, the research makes a number of findings; one of which is the reinforcement that leadership is of paramount importance to organisations, other findings include; the contributions young founder-leaders make to the culture of their organisations as well as the positive effects they have on their employees.